2008
DOI: 10.1080/13880200802055834
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Human Serum Paraoxonase and Effect of Acetylsalicylic Acid on Paraoxonase Activity

Abstract: Paraoxonase was purified from human serum using sepharose-4B-L-tyrosine-1-napthylamine affinity chromatography. This enzyme was purified 1797-fold. SDSpolyacrylamide electrophoresis of the enzyme indicates a single protein staining band with an apparent Mr of 43 kDa. The kinetic properties of the purified enzyme were determined. The V max and K m are 231.5 µ/mg protein (EU) and 3.96 mM using substrate paraoxon respectively. The effect of acetylsalicylic acid on purified human serum paraoxonase has been investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…For this purpose, some research groups focused on the effects of known compounds on PON1 activity. Aliphatic alcohols, some metal ions, acetylsalicylic acid, coumarin derivatives, anaesthetics, antibiotics, calcium channel blockers, cardiovascular therapeutics, some anticancer agents, some pesticides, some copper complexes, sulfonamide derivatives and antiepileptic drugs have been investigated by various research groups in view of their possible effects on PON1 activity. Additionally, our group investigated the PON1 inhibitory properties of imidazolium salts with coumarin, benzoxazinone or benzotriazole moieties and we showed that coumarin‐substituted imidazolium salts are stronger inhibitors of PON1 than corresponding 4‐chloromethylene coumarins .…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, some research groups focused on the effects of known compounds on PON1 activity. Aliphatic alcohols, some metal ions, acetylsalicylic acid, coumarin derivatives, anaesthetics, antibiotics, calcium channel blockers, cardiovascular therapeutics, some anticancer agents, some pesticides, some copper complexes, sulfonamide derivatives and antiepileptic drugs have been investigated by various research groups in view of their possible effects on PON1 activity. Additionally, our group investigated the PON1 inhibitory properties of imidazolium salts with coumarin, benzoxazinone or benzotriazole moieties and we showed that coumarin‐substituted imidazolium salts are stronger inhibitors of PON1 than corresponding 4‐chloromethylene coumarins .…”
Section: Resultsmentioning
confidence: 99%
“…to separate serum. The obtained serum was used to purify PON1 enzyme via the three-phase separation method [27,28].…”
Section: Purification and Enzymatic Properties Of Pon1 Enzymementioning
confidence: 99%
“…The reactions were incubated for 15 minutes at 37 o C and the absorbance changes were recorded at 412 nm and enzymes activities were determined. The % Activity-Inhibitor concentration graphs were plotted versus three drugs using the obtained data and IC50 values were calculated (Table 4) [27,28,38].…”
Section: In Vitro Investigation Of the Effects Of Antilipid Drugs And...mentioning
confidence: 99%
“…Activity measurement is based on establishing the changes in absorption of formed p-nitrophenol as a result of the reaction of PON1 with paraoxon at 412 nm. p-Nitrophenol the molar extinction coefficient is e = 18.290M −1 cm −1 and an enzyme unit is number of micromole of hydrolysis paraoxon in per minute [41][42][43].…”
Section: 22mentioning
confidence: 99%
“…Human paraoxonase 1 was eluted with the solution 25 mM Tris/HCl (pH 8.0)/10 mM CaCl 2 at 0.5mL/min. Fractions (3 mL each) were collected as 3 mL, and those with the highest PON1 activity were combined [42,43].…”
Section: Sepharose 4b-l-tyrosine-1-naphthylamine Affinity Chromatographmentioning
confidence: 99%